Generalised osteitis fibrosa cystica due to secondary hyperparathyroidism in chronic kidney disease - Shrestha, Sundar K; Tayal, A (Journal of College of Medical Sciences-Nepal, 2014)
Secondary hyperparathyroidism is a frequent complication of patients with chronic kidney disease and is characterized by excessive serum parathyroid hormone levels and an imbalance in calcium and phosphorus metabolism. Secondary hyperparathyroidism is the leading cause of renal osteodystrophy and bone disease. Osteitis fibrosa cystica, the classic and former most common osteodystrophy, is mainly caused by high bone turnover secondary to high levels of circulating PTH. Its pathophysiology is mainly due to hyperphosphatemia and vitamin D deficiency and resistance. This condition has a high impact on the mortality and morbidity of dialysis patients Hyperparathyroidism develops early in the course of CKD and becomes more prominent as kidney function declines. However recently, with the technical development of imaging and laboratory screening methods, hypercalcemia due to primary or secondary hyperparathyroidism can often be detected early; as a result the frequency of osteitis fibrosa cystica has declined. Journal of College of Medical Sciences-Nepal, 2013, Vol-9, No-1, 60-66 DOI: http://dx.doi.org/10.3126/jcmsn.v9i1.9676